Silicon-carbon composite material, preparation method thereof, pole piece, application and electrochemical device

By calcining the silica source, magnesium powder and carbon source in one step, a silicon-carbon composite material with smaller particle size was prepared, which solved the problems of high preparation costs and poor circulation and maintenance performance in the prior art, and achieved high efficiency of the battery Chemical properties and simplified preparation process.

CN119447268APending Publication Date: 2025-02-14NINGBO SHANSHAN SILICON-BASED MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411731932.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have high preparation costs and cumbersome preparation methods, resulting in poor circulation and maintenance performance of assembled batteries.

Method used

The silicon dioxide source, magnesium powder and carbon source were mixed with one-step method and then calcined. Through the synergistic effect of magnesium thermal reduction and carbon source decomposition, a silicon-carbon composite material with smaller particle size was prepared, which simplified the preparation process and reduced the cost.

Benefits of technology

The prepared silicon-carbon composite material has a small particle size, and the assembled batteries have better electrochemical properties, especially the circulation and maintenance performance is significantly improved, the raw materials are widely sourced, the cost is low, and the preparation process is simple and easy to operate and has high safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447268A_ABST
    Figure CN119447268A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material, a preparation method thereof, a pole piece, application and an electrochemical device. The preparation method of the silicon-carbon composite material comprises the following steps that a one-step method is adopted, a mixture is calcined, and the mixture comprises a silicon dioxide source, magnesium powder and a carbon source; the molar ratio of the silicon dioxide source to the magnesium powder to the carbon source is 1: (1-6): (0.5-2). The silicon-carbon composite material prepared by the invention is small in particle size, and the battery assembled by the silicon-carbon composite material has better electrochemical performance, especially has better cycle retention performance. The silicon-carbon composite material prepared by the invention is wide in raw material source, low in cost and pollution-free, and the preparation process is simple, easy to operate and relatively high in safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method, a pole piece, an application and an electrochemical device thereof. Background Art

[0002] Graphite is a traditional negative electrode material for lithium-ion batteries. -1 The theoretical specific capacity of silicon can no longer meet people's demand for high specific capacity batteries. -1 Silicon is considered to be the next generation of new lithium-ion battery negative electrode materials due to its theoretical specific capacity (more than 10 times that of graphite), suitable lithium insertion platform, abundant natural resources and other advantages. However, silicon will produce a huge volume expansion (about 300%) during the lithium insertion process, which will lead to the destruction of the electrode structure, rapid capacity decay, and instability of the solid electrolyte interface (SEI), thereby reducing the coulombic efficiency and cycle life of the battery. Silicon has poor conductivity, which makes the high current charge and discharge performance of the battery less than ideal, seriously affecting the commercial application of silicon negative electrode materials. To solve the above problems, silicon materials are porous and carbon-coated surface modified. Porosity can effectively alleviate the volume expansion of silicon during the lithium insertion and deintercalation process and improve the structural stability of the electrode. Carbon-coated surface modification can limit the volume expansion of silicon, prevent direct contact between silicon and electrolyte, reduce the occurrence of side reactions, and at the same time increase the transmission rate of lithium ions and electrons and improve the conductivity of the material.

[0003] Most of the existing technical routes for preparing porous silicon materials have problems such as high cost of silicon source raw materials, complex technical routes, multi-step processes for material preparation, high requirements for equipment conditions, and poor product reproducibility. For example, in patent CN202310177210.7, a method for synthesizing a porous silicon-carbon composite material by a solid-phase method in one step and the application of the porous silicon-carbon composite material, the silicon source is magnesium silicide, and the material cost is relatively high, which is not suitable for commercial production. Patent CN202111164035.5 Silicon-containing mineral-based porous silicon-carbon composite negative electrode material and preparation method thereof. The nano-silicon used in this method has a high cost, and the material preparation method is cumbersome and complicated. Patent CN202311197774.3 A porous silicon-carbon composite negative electrode material and its preparation method and application. This method requires the use of toxic and high-cost silicon tetrachloride gas as a silicon source, and the output is low, which cannot meet commercial large-scale production. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art silicon-carbon composite materials, such as high preparation cost, cumbersome preparation method, and large particle size of the silicon-carbon composite materials, which leads to poor cycle retention performance of the battery assembled therefrom, and provide a silicon-carbon composite material and its preparation method, pole piece, application and electrochemical device. The silicon-carbon composite material prepared by the present invention has a small particle size, and the battery assembled from the silicon-carbon composite material has better electrochemical performance, especially better cycle retention performance. When preparing the silicon-carbon composite material by the present invention, the raw material source is wide, the cost is low, there is no pollution, and the preparation process is simple, easy to operate, and has high safety.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps: adopting a one-step method to calcine a mixture, wherein the mixture comprises a silicon dioxide source, magnesium powder and a carbon source; and the molar ratio of the silicon dioxide source, magnesium powder and carbon source is 1:(1-6):(0.5-2).

[0007] In the present invention, the one-step method means mixing the silica source, the carbon source and the magnesium powder together and then calcining them, which is different from the two-step method in the prior art (i.e., first mixing the silica and magnesium powder and calcining them, then adding the carbon source and calcining them again).

[0008] In the present invention, the source of the silicon dioxide source can be a conventional silicon dioxide-containing raw material in the art, preferably one or more of silicon dioxide, quartz sand, straw, corn leaves, rice husks, glass, ceramics and diatomaceous earth, such as silicon dioxide or quartz sand. The mass content of silicon dioxide in the quartz sand can be greater than 90%.

[0009] In the present invention, the D50 of the silicon dioxide source may be 1-10 μm, for example, 3-5 μm.

[0010] In the present invention, the silicon dioxide source can be ball-milled to obtain the target D50. The equipment for ball milling can be conventional in the art, such as a ball mill. The rotation speed during ball milling can be 400-600 rpm, such as 500 rpm. The time of ball milling can be 9-11 hours, such as 10 hours. The ball-to-material ratio during ball milling can be (15-25):1, such as 20:1.

[0011] In the present invention, the carbon source may be a conventional carbonate in the art that can be decomposed at 600-900° C., preferably one or more of magnesium carbonate, sodium carbonate and calcium carbonate, such as calcium carbonate.

[0012] In the present invention, the D50 of the carbon source may be 1-10 μm, for example 3-5 μm.

[0013] In the present invention, the carbon source can be ball milled to obtain the target D50. The equipment for ball milling can be conventional in the art, such as a ball mill. The rotation speed during ball milling can be 400-600 rpm, such as 500 rpm. The time of ball milling can be 9-11 hours, such as 10 hours. The ball-to-material ratio during ball milling can be (15-25):1, such as 20:1.

[0014] In the present invention, the preparation method of the mixture is preferably: firstly mixing the silicon dioxide source and the carbon source, and then secondly mixing with the magnesium powder.

[0015] Wherein, the first mixing method may be conventional in the art, such as ball milling. The equipment for the ball milling may be conventional in the art, such as a ball mill. The rotation speed during the ball milling may be 500-700 rpm, such as 600 rpm. The time of the ball milling may be 4-6 hours, such as 5 hours. The ball-to-material ratio during the ball milling may be (15-25):1, such as 20:1. The molar ratio of the silicon dioxide source to the carbon source may be 1:(0.5-2), preferably 1:(0.8-1.5), such as 1:1.

[0016] Wherein, the second mixing method may be conventional in the art, such as ball milling. The equipment for the ball milling may be conventional in the art, such as a ball mill. The rotation speed during the ball milling may be 100-300 rpm, such as 200 rpm. The time of the ball milling may be 1-3 h, such as 2 h. The ball-to-material ratio during the ball milling may be (15-25):1, such as 20:1. The molar ratio of the silicon dioxide source to the magnesium powder may be 1:(1-6), preferably 1:(3-5), such as 1:4.

[0017] In the present invention, the molar ratio of the silica source, magnesium powder and carbon source is preferably 1:4:1, 1:1:0.5, 1:1:2, 1:6:0.5 or 1:6:2.

[0018] In the present invention, the calcining equipment can be conventional in the art, such as a tube furnace. During the calcining, the mixture is preferably placed in a porcelain boat.

[0019] In the present invention, the calcination is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon, or argon and hydrogen. When the inert atmosphere is argon and hydrogen, the volume percentage of argon is preferably 90%-98%, for example 95%.

[0020] In the present invention, the calcination temperature may be 600-900°C, such as 700 or 800°C.

[0021] In the present invention, the calcination time may be 2-10 hours, preferably 5-7 hours, for example 6 hours.

[0022] In the present invention, the calcination preferably further includes the steps of cooling, first washing, centrifugation, second washing and drying.

[0023] Wherein, the cooling method can be conventional in the art, such as natural cooling. The cooling is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon and / or hydrogen. When the inert atmosphere is argon and hydrogen, the volume percentage of argon is preferably 90%-98%, such as 95%. The end point of the cooling is preferably room temperature, generally 20-30°C.

[0024] Wherein, the first washing method can be conventional in the art, such as pickling. The pickling is preferably washed with hydrochloric acid aqueous solution and / or hydrofluoric acid aqueous solution. The molar concentration of the acid solution used in the pickling can be 1-3 mol / L, for example 2 mol / L. The first washing is preferably first washed with 1 mol / L hydrochloric acid aqueous solution, and then washed with 3 mol / L hydrofluoric acid aqueous solution.

[0025] The centrifugal operation may be conventional in the art, for example, performed in a centrifuge. The speed of the centrifugal operation may be 700-900 rpm, for example, 800 rpm. The centrifugal time may be 1-3 min, for example, 2 min.

[0026] The second washing method may be conventional in the art, such as water washing and / or alcohol washing. The alcohol in the alcohol washing is preferably ethanol. The second washing is preferably performed by first washing with water for 3 times and then washing with sewage ethanol for 1 time.

[0027] The drying operation may be conventional in the art, such as vacuum drying. The drying temperature may be 50-70° C., such as 60° C. The drying time may be 9-11 h, such as 10 h.

[0028] In the present invention, a one-step method is adopted, and the exothermic reaction of magnesium thermal reduction and the endothermic reaction of carbon source decomposition form a synergistic effect, and the carbon source generates carbon dioxide when decomposing to form a carbon layer in situ on the surface of silicon, which can effectively alleviate the particle sintering and agglomeration phenomenon caused by local heat release of magnesium thermal reduction reaction during the reaction process, and omit the process of carbon coating modification on the surface of silicon-carbon material. Only when the reasonable amount of silicon dioxide source, magnesium powder and carbon source is selected, the heat balance of exothermic reaction and endothermic reaction can be achieved, and the particle size of the obtained silicon-carbon composite material can be effectively controlled.

[0029] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method as described above.

[0030] In the present invention, the silicon-carbon composite material comprises porous silicon and a carbon layer coated on the surface of the porous silicon.

[0031] The thickness of the carbon layer may be 5-15 nm, preferably 8-12 nm, such as 11 nm.

[0032] In the present invention, the average pore size of the silicon-carbon composite material may be 20-40 nm, preferably 20-35 nm, such as 20.1 or 34.7 nm.

[0033] In the present invention, the D50 of the silicon-carbon composite material may be 4-6 μm, for example, 4.2, 4.6, 4.3, 5.5, 4.8 or 4.1 μm.

[0034] In the present invention, the specific surface area of ​​the silicon-carbon composite material can be 60-130m 2 / g, preferably 70-128m 2 / g, such as 73.1 or 125.4m 2 / g.

[0035] In the present invention, the mass content of carbon in the silicon-carbon composite material may be 25-35%, preferably 25-30%, for example 28.77%.

[0036] In the present invention, the mass content of silicon in the silicon-carbon composite material may be 60-70%, preferably 61-65%, for example 61.25%.

[0037] In the present invention, the mass content of oxygen in the silicon-carbon composite material may be 5-12%, preferably 8-10%, for example 9.98%.

[0038] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0039] In the present invention, preferably, the electrode sheet is a negative electrode sheet.

[0040] The present invention also provides an application of the pole piece as described above in an electrochemical device.

[0041] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0042] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0043] The reagents and raw materials used in the present invention are commercially available.

[0044] The positive and progressive effects of the present invention are:

[0045] (1) The silicon-carbon composite material prepared by the present invention has a small particle size, and the battery assembled from the silicon-carbon composite material has better electrochemical performance.

[0046] (2) The raw materials of the present invention are widely available, low in cost, pollution-free, and the preparation process is simple, easy to operate, and highly safe. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The particle size distribution diagrams of silicon dioxide, calcium carbonate, the silicon-carbon composite material prepared in Example 1 and the silicon-carbon composite material prepared in Comparative Example 1 are shown respectively; wherein, Figure 1 Part a is a particle size distribution diagram of silicon dioxide and the silicon-carbon composite material obtained in Comparative Example 1, Figure 1 Part b is a particle size distribution diagram of silicon dioxide, calcium carbonate, and the silicon-carbon composite material prepared in Example 1.

[0048] Figure 2 The XRD spectra and energy spectra of silicon dioxide, calcium carbonate and the silicon-carbon composite material prepared in Example 1 are respectively; wherein, Figure 2 Part a is the XRD spectrum of silicon dioxide, calcium carbonate and the silicon-carbon composite material prepared in Example 1, Figure 2 Part b is the energy spectrum of the silicon-carbon composite material obtained in Example 1.

[0049] Figure 3 They are respectively the thermogravimetric test graph and Raman spectrum graph of the silicon-carbon composite material obtained in Example 1; wherein, Figure 3 Part a is a thermogravimetric test diagram of the silicon-carbon composite material obtained in Example 1. Figure 3 Part b is the Raman spectrum of the silicon-carbon composite material prepared in Example 1.

[0050] Figure 4 They are respectively the microscopic morphology and elemental analysis diagram of the silicon-carbon composite material obtained in Example 1; wherein, Figure 4 Part a is a SEM image of the silicon-carbon composite material obtained in Example 1. Figure 4 Part b is an elemental analysis diagram of carbon element in the SEM image of the silicon-carbon composite material obtained in Example 1. Figure 4 Part c is an elemental analysis diagram of silicon element in the SEM image of the silicon-carbon composite material prepared in Example 1, Figure 4 Part d is a transmission electron microscope image of the silicon-carbon composite material obtained in Example 1. Figure 4 Part e is a partial enlarged transmission electron microscope image of the silicon-carbon composite material obtained in Example 1. Figure 4 Part f is the selected area electron diffraction pattern of the silicon-carbon composite material obtained in Example 1, Figure 4 Part g is a transmission electron microscope dark field image of the silicon-carbon composite material obtained in Example 1. Figure 4 Part h is the element distribution diagram of carbon element in the transmission electron microscope of the silicon-carbon composite material obtained in Example 1. Figure 4Part i is the element distribution diagram of silicon element in the silicon-carbon composite material prepared in Example 1 under a transmission electron microscope.

[0051] Figure 5 The graphs are the test results of the specific surface area and pore size of the silicon-carbon composite material obtained in Example 1; wherein, Figure 5 Part a is a graph showing the specific surface area test results of the silicon-carbon composite material obtained in Example 1. Figure 5 Part b is a graph showing the test results of the pore size of the silicon-carbon composite material obtained in Example 1.

[0052] Figure 6 The electrochemical performance curves of the silicon-carbon composite material obtained in Example 1 are shown respectively; wherein, Figure 6 Part a is the cyclic voltammetry curve of the silicon-carbon composite material obtained in Example 1, Figure 6 Part b is the charge-discharge curve of the silicon-carbon composite material obtained in Example 1 during the first three weeks. Figure 6 Part c is a cycle performance curve of the silicon-carbon composite material obtained in Example 1, Figure 6 Part d is the rate performance diagram of the silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0053] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0054] Example 1

[0055] (1) Silica (200 mesh, analytical grade (AR)) and calcium carbonate were ball milled in a ball mill at 500 rpm for 10 h, with a ball-to-material ratio of 20:1, until the D50 of calcium carbonate and silica was 3-5 μm;

[0056] (2) The silicon dioxide and calcium carbonate ball-milled in step (1) are first mixed by ball milling, wherein the molar ratio of silicon dioxide to calcium carbonate is 1:1 and the ball-to-material ratio is 20:1, and the mixture is ball milled at a speed of 600 rpm for 5 h to obtain a mixed product A;

[0057] (3) The mixed product A after ball milling in step (2) was mixed with magnesium powder in a molar ratio of 2:4 (the molar ratio of silicon dioxide, calcium carbonate and magnesium powder was 1:1:4) in a ball mill at a speed of 200 rpm for a second mixing for 2 h to obtain a mixed product B, with a ball-to-material ratio of 20:1;

[0058] (4) The mixed product B in step (3) is placed in a porcelain boat and calcined in a tube furnace at 800° C. under argon for 6 h, and then naturally cooled to room temperature under argon to obtain a calcined product.

[0059] (5) The calcined product obtained in step (4) was heated to 1 mol L -1 The byproducts of the reaction, magnesium oxide, calcium oxide, magnesium silicide and unreacted calcium carbonate, were removed by pickling with 3 mol L -1 The unreacted silicon dioxide was removed by aqueous hydrofluoric acid solution, and then centrifuged at 800 rpm for 2 minutes using a Cence TG16-WS desktop high-speed centrifuge, washed 3 times with deionized water, and washed once with anhydrous ethanol. The centrifuged material and the centrifuge tube were placed in a Jinghong DZF-6050 vacuum drying oven (pressure: -0.1Mpa) and dried at 60°C for 10 hours to obtain a silicon-carbon composite material.

[0060] Example 2

[0061] The only difference from Example 1 is that in step (3), the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:0.5:1.

[0062] Example 3

[0063] The only difference from Example 1 is that in step (3), the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:2:1.

[0064] Example 4

[0065] The only difference from Example 1 is that in step (3), the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:0.5:6.

[0066] Example 5

[0067] The only difference from Example 1 is that the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:2:6.

[0068] Example 6

[0069] The only difference from Example 1 is that the silicon dioxide in Example 1 is replaced by quartz sand (the content of silicon dioxide in quartz sand is greater than 90%).

[0070] Comparative Example 1

[0071] (1) Silica (200 mesh, analytical grade (AR)) was ball milled in a ball mill at 500 rpm for 10 h with a ball-to-material ratio of 20:1 until the silica D50 was 3-5 μm;

[0072] (2) The silicon dioxide ball-milled in step (1) was ball-milled again, with a ball-to-material ratio of 20:1, and the ball-milling was performed at a speed of 600 rpm for 5 h;

[0073] (3) The silicon dioxide and magnesium powder ball-milled in step (2) were ball-milled at a molar ratio of 1:4 in a ball mill at a speed of 200 rpm for 2 h to obtain a mixed product, with a ball-to-material ratio of 20:1;

[0074] (4) The mixed product in step (3) is placed in a porcelain boat and calcined in a tube furnace at 800° C. under argon for 6 h, and the temperature is naturally lowered under argon to obtain a calcined product.

[0075] (5) The calcined product obtained in step (4) was heated to 1 mol L -1 The reaction products magnesium oxide and magnesium silicide were removed by pickling with hydrochloric acid, and then 3 mol L -1 The unreacted silicon dioxide is removed by hydrofluoric acid, and then the silicon material is obtained by centrifugation and vacuum drying.

[0076] (6) Weigh 96 mg of tris(hydroxymethyl)aminomethane powder in a beaker, add 100 mg of the silicon material obtained in step (5), then add 80 mL of deionized water and stir magnetically for 20 min at room temperature, then weigh 100 mg of dopamine hydrochloride and add it to the above solution, continue stirring for 4 h, centrifuge, wash with water and ethanol three times, and dry in a vacuum drying oven. The dried powder was calcined in a tube furnace at 550°C under argon atmosphere for 3 h to obtain a silicon-carbon composite material.

[0077] Comparative Example 2

[0078] A two-step method was used: (1) silica (200 mesh, analytical grade (AR)) was ball-milled in a ball mill at 500 rpm for 10 h with a ball-to-material ratio of 20:1 to reduce the silica D50 to 3–5 μm;

[0079] (2) mixing the milled silica with magnesium powder (the molar ratio of silica to magnesium powder is 1:4), and milling the mixture in a ball mill at 200 rpm for 2 h to obtain a mixed product B, with a ball-to-material ratio of 20:1;

[0080] (3) The mixed product B in step (2) is placed in a porcelain boat and calcined in a tube furnace at 800° C. under argon for 6 h, and then naturally cooled under argon to obtain a calcined product.

[0081] (4) Add calcium carbonate (the molar ratio of calcium carbonate to magnesium powder is 1:4) to the mixture obtained in step (3), mix well, and calcine in a tube furnace at 800° C. under argon for 6 h. Then, cool naturally to room temperature under argon to obtain a calcined product.

[0082] (5) After the calcined product obtained in step (4) is -1The reaction byproducts, magnesium oxide, calcium oxide, magnesium silicide and unreacted calcium carbonate, were removed by pickling in a hydrochloric acid aqueous solution, and then 3 mol L -1 The unreacted silicon dioxide was removed by aqueous hydrofluoric acid solution, and then centrifuged at 800 rpm for 2 minutes using a Cence TG16-WS desktop high-speed centrifuge, washed 3 times with deionized water, and washed once with anhydrous ethanol. The centrifuged material and the centrifuge tube were placed in a Jinghong DZF-6050 vacuum drying oven (pressure: -0.1Mpa) and dried at 60°C for 10 hours to obtain a silicon-carbon composite material.

[0083] Comparative Example 3

[0084] The only difference from Example 4 is that the only difference from Example 1 is that the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:0.1:6.

[0085] Comparative Example 4

[0086] The only difference from Example 4 is that the molar ratio of silicon dioxide, calcium carbonate and magnesium powder is 1:10:6.

[0087] Effect Example 1

[0088] The particle size distribution of silicon dioxide, calcium carbonate, the silicon-carbon composite materials prepared in Examples 1-6 and the silicon-carbon composite materials prepared in Comparative Examples 1-4 was tested respectively using a Mastersizer 3000 laser particle size analyzer. Figure 1 And as shown in Table 1.

[0089] Test results such as Figure 1 Part a and Figure 1 As shown in part b of Figure 1 It can be seen that the silica particle size D50 before the reaction is 3.3 µm, the calcium carbonate particle size D50 is 5.1 µm, and the particle size of the silicon-carbon composite material obtained in Comparative Example 1 is sintered and agglomerated into large particles with a D50 of 30.6 μm, which seriously affects the electrochemical properties of the material. The particle size D50 of the silicon-carbon composite material obtained in Example 1 is 4.2 μm, indicating that the heat released by the magnesium thermal reaction during the reaction is absorbed by calcium carbonate for the decomposition of calcium carbonate, which not only alleviates the sintering and agglomeration problem caused by local heat release during the magnesium thermal reduction process, but also the material exothermic and endothermic distribution is uniform, and no sintering and agglomeration occurs.

[0090] Table 1

[0091]

[0092] Effect Example 2

[0093] The silicon dioxide, calcium carbonate and the silicon-carbon composite material prepared in Example 1 were subjected to XRD test, and the results were as follows: Figure 2 As shown in part a of Figure 2 From the a part, we can see that the black curve ① is the XRD spectrum of calcium carbonate, which has obvious characteristic peaks at 2θ of 29.4, 39.4, 47.5 and 48.5 degrees, which corresponds to the (104) (113) (018) (116) peaks of calcium carbonate in JCPDS No.47-1743; the red curve ② is the XRD spectrum of silicon dioxide, which has obvious characteristic peaks at 2θ of 20.5, 26.2, 35.9, 38.9, 41.68 and 58.9 degrees, which corresponds to the (104) (113) (018) (116) peaks of calcium carbonate in JCPDS No.47-1743. The peak positions of the (100) (011) (110) (102) (200) (211) planes of No.47-1144 silicon dioxide; the blue curve ③ is the XRD spectrum of the silicon-carbon composite material, which has obvious characteristic peaks at 2θ of 28.4, 47.3, 56.1 and 76.3 degrees, respectively. These peaks correspond to the (111) (220) (311) (331) diffraction peaks of JCPDS No.27-1402 silicon. It can be seen that there are no other impurities in the composite silicon-carbon material.

[0094] Figure 2 Part b is the energy spectrum of the silicon-carbon composite material obtained in Example 1. It can be seen from the figure that the main element in the silicon-carbon composite material is silicon, carbon accounts for 28.77%, and it also contains a small amount of oxygen. This may be because it is difficult to avoid a small amount of oxidation on the fresh surface of silicon during the preparation process.

[0095] The silicon-carbon composite material prepared in Example 1 was subjected to a thermogravimetric test (the test equipment was a STA 449F3 thermogravimetric analyzer, the test atmosphere was air, and the heating rate was 10° C. min -1 ) and Raman spectroscopy (the test equipment is the RM5 Raman spectrometer produced in Edinburgh, UK). The results are as follows Figure 3 As shown by Figure 3 From part a, it can be seen that the carbon content of the silicon-carbon composite material prepared in Example 1 is 21.4%. Figure 3 Part b is the Raman scattering spectrum of the silicon-carbon composite material. It can be observed from the figure that there are silicon peaks and carbon D peaks and G peaks in the silicon-carbon composite material, indicating that the material prepared in Example 1 is indeed a silicon-carbon composite material.

[0096] The microscopic morphology of the silicon-carbon composite material obtained in Example 1 was observed. Figure 4 It is knowable. Figure 4 Part a is a SEM image of the silicon-carbon composite material, and it can be clearly seen that the silicon-carbon composite material presents a porous structure. Figure 4Part b and part c are element analysis images of the silicon-carbon composite material. It can be seen that carbon and silicon elements are evenly distributed in the silicon-carbon composite material. Figure 4 Part d is a transmission electron microscope image of the silicon-carbon composite material. From the image, it can still be clearly seen that the silicon-carbon composite material has many porous structures. Figure 4 The e part is Figure 4 From the enlarged image of part d, we can see that the silicon layer and the carbon layer have a clear interface. The lattice stripes on the right are the silicon region, with a lattice spacing of 0.31 nm, corresponding to the (111) crystal plane of silicon. The amorphous region on the left is the amorphous carbon layer, which is evenly coated on the surface of silicon, and the thickness of the carbon layer is 11 nm. Figure 4 Part f is the selected area electron diffraction of the silicon-carbon composite material. Obvious diffraction spots of silicon can be seen, corresponding to the (111), (220) and (311) crystal planes of silicon, respectively, indicating that the silicon-carbon composite material prepared in Example 1 does include silicon material. Figure 4 Parts g, h, and i are the transmission electron microscope dark field images and elemental analysis of the silicon-carbon composite material, respectively. It can be seen that the silicon and carbon elements are evenly distributed.

[0097] The silicon-carbon composite materials prepared in Examples 1-2 and Comparative Example 4 were tested for specific surface area and pore size using an ASAP2460 surface area analyzer produced by Micrometrics. Figure 5 It is knowable. Figure 5 Part a and part b are the nitrogen adsorption-desorption curve and pore size distribution curve of the silicon-carbon composite material, respectively. It can be seen that the nitrogen adsorption-desorption curve has a hysteresis loop. From the numerical value, it can be seen that its specific surface area is 125.4m 2 g -1 , and its average pore size is 20.1nm.

[0098] Table 2

[0099]

[0100] Effect Example 3

[0101] The lithium storage performance test of the silicon-carbon composite material prepared in the embodiment and the comparative example adopts a 2032 type button half-cell. The negative electrode plate is respectively made of the silicon-carbon composite material prepared in embodiment 1-6 or comparative example 1-4 as the active material, acetylene black as the conductive agent, and sodium carboxymethyl cellulose (CMC) as the binder, and the three are dispersed in deionized water in a mass ratio of 7:1.5:1.5 to form a slurry. The slurry is evenly coated on the copper foil and dried at 60°C in a vacuum drying oven for 10 h. The button battery assembly is completed in an argon glove box, and a lithium sheet is used for the electrode. The electrolyte is 1M lithium hexafluorophosphate (LiPF6) dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 (EC:DEC=1:1, v / v), and 3% volume fraction of fluoroethylene carbonate (FEC) is added as an electrolyte additive. The diaphragm is Celgard2500, and its thickness is 25 μm.

[0102] The assembled button cell was packaged and placed in a glove box for 12 h. Cyclic voltammetry was performed on an electrochemical workstation (CHI 660D) with a scan rate of 0.1 mV s -1 , the scanning range is 0.01-1.0 V. During the test, the working electrode (WE) is connected to the electrode on the active material side, the counter electrode (CE) and the reference electrode (RE) are connected to the electrode on the lithium sheet side, and the scanning is performed for three cycles.

[0103] After standing for 12 hours, connect the battery to the Blue Electric charge and discharge tester for constant current charge and discharge test. The cut-off voltage for button battery charge and discharge is 0.01V-1.0V, and the test steps are standing, constant current discharge, constant current charge, and the cycle is three cycles.

[0104] After standing for 12 hours, connect the battery to the Blue Electric Charge and Discharge Tester for constant current charge and discharge test. The cut-off voltage for button battery charge and discharge is 0.01V-1.0V. A small current (0.2 A g) is used for the first five weeks. -1 ) charge and discharge test, activation, and high current (0.5 A g -1 ) cycle, and long cycle performance can determine the cycle stability of silicon-carbon composite materials.

[0105] The rate performance test procedure is to test the battery at 0.2 A g -1 , 0.5 A g -1 , 1.0 A g -1 , 2.0 A g -1 , 4.0 Ag -1 , 8.0 A g -1 The constant current charge and discharge cycles were repeated 10 times, and the high rate test was performed at 0.2 A g -1 Constant current charge and discharge test.

[0106] The results are as follows Figure 6 And as shown in Table 3.

[0107] Table 3

[0108]

[0109] Figure 6 Part a is the cyclic voltammetry curve of the silicon-carbon composite material obtained in Example 1. By observing the curve, it can be found that the reduction peak of 0.15V in the lithium insertion process of each cycle corresponds to the alloying reaction of Li and Si. The two oxidation peaks of 0.3V and 0.5V in the lithium removal process correspond to the Li x The dealloying reaction of Si alloy is consistent with the charge and discharge characteristics of silicon-carbon negative electrode.

[0110] Figure 6 Part b is the charge-discharge curve of the silicon-carbon composite material obtained in Example 1 in the first three weeks, and the discharge capacity is 2496.9 mAh g -1 The first week charging capacity is 1945.2 mAh g -1 The first Coulomb efficiency (ICE) is 77.90%, and the efficiency is relatively high in the first week.

[0111] from Figure 6 As can be seen from part c, the battery prepared from the silicon-carbon composite material prepared in Example 1 has a current density of 0.2 A g in the first five weeks. -1 Its reversible capacity is 1950.3 mAh g -1 At 0.5 A g -1 After 200 cycles at a current density of 1.34 W, the reversible capacity is 1286.1 mAh g -1 The capacity retention rate was 85.7% (compared with the reversible capacity of 1501.7 mAh g in the sixth week). -1 contrast).

[0112] The battery prepared from the silicon-carbon composite material obtained in Comparative Example 1 has a higher initial capacity of 2213.5 mAhg -1 , but at 0.5 A g -1 After 200 cycles at a current density of 1.34 Å, the reversible capacity is only 1016.7 mAh g -1 The capacity retention rate was 59.0% (compared with the reversible capacity of 1723.1 mAh g in the sixth week). -1 Comparison), showing the superiority of the cycle performance of the silicon-carbon composite material prepared in Example 1.

[0113] Figure 6 The d part shows the rate performance of the silicon-carbon composite material prepared in Example 1. The rate performance of the silicon-carbon composite material prepared in Example 1 is good.-1 , 0.5 A g -1 , 1.0 A g -1 , 2.0 A g -1 , 4.0 A g -1 , 8.0 A g -1 At current densities of 2013 mAh g -1 、1698 mAh g -1 , 1485 mAh g -1 、1143 mAh g -1 , 830 mAh g -1 reversible capacity.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The method comprises the following steps: adopting a one-step method to calcine a mixture, wherein the mixture comprises a silicon dioxide source, magnesium powder and a carbon source; and the molar ratio of the silicon dioxide source, magnesium powder and carbon source is 1:(1-6):(0.5-2).

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1) to (4): (1) The molar ratio of the silicon dioxide source, magnesium powder and carbon source is 1:4:1, 1:1:0.5, 1:1:2, 1:6:0.5 or 1:6:2; (2) The calcination is carried out under an inert atmosphere; the inert atmosphere is preferably argon, or argon and hydrogen; when the inert atmosphere is argon and hydrogen, the volume percentage of argon is preferably 90%-98%, for example 95%; (3) the calcination temperature is 600-900°C, for example 700 or 800°C; and, (4) The calcination time is 2-10 hours, preferably 5-7 hours, for example 6 hours.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1) to (4): (1) The source of the silicon dioxide source is one or more of silicon dioxide, quartz sand, straw, corn leaves, rice husks, glass, ceramics and diatomaceous earth, such as silicon dioxide or quartz sand; (2) The D50 of the silica source is 1-10 μm, for example 3-5 μm; (3) the carbon source is a carbonate that can be decomposed at 600-900°C, preferably one or more of magnesium carbonate, sodium carbonate and calcium carbonate, such as calcium carbonate; and, (4) The D50 of the carbon source is 1-10 μm, for example 3-5 μm.

4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The mixture is prepared by first mixing a silicon dioxide source and a carbon source, and then mixing them with magnesium powder; Wherein, the first mixing method is preferably ball milling; the ball milling equipment is preferably a ball mill; the rotation speed during the ball milling is preferably 500-700 rpm, such as 600 rpm; the ball milling time is preferably 4-6 hours, such as 5 hours; the ball-to-material ratio during the ball milling is preferably (15-25):1, such as 20:1; the molar ratio of the silicon dioxide source to the carbon source is preferably 1:(0.5-2), more preferably 1:(0.8-1.5), such as 1:1; Among them, the second mixing method is preferably ball milling; the ball milling equipment is preferably a ball mill; the rotation speed during ball milling is preferably 100-300rpm, for example, 200rpm; the ball milling time is preferably 1-3h, for example, 2h; the ball-to-material ratio during ball milling is preferably (15-25):1, for example, 20:1; the molar ratio of the silicon dioxide source to the magnesium powder is preferably 1:(1-6), more preferably 1:(3-5), for example, 1:

4.

5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: After the calcination, the steps of cooling, first washing, centrifugation, second washing and drying are also included; The cooling method is preferably natural cooling; the cooling is preferably carried out under an inert atmosphere; the inert atmosphere is preferably argon, or argon and hydrogen; when the inert atmosphere is argon and hydrogen, the volume percentage of argon is preferably 90%-98%, for example 95%; the end point of the cooling is preferably 20-30°C; Wherein, the first washing method is preferably pickling; the pickling is preferably washed with hydrochloric acid aqueous solution and / or hydrofluoric acid aqueous solution; the molar concentration of the acid solution used in the pickling is preferably 1-3 mol / L, for example, 2 mol / L; the first washing is preferably first washed with 1 mol / L hydrochloric acid aqueous solution, and then washed with 3 mol / L hydrofluoric acid aqueous solution; The centrifugation operation is preferably performed in a centrifuge; the speed of the centrifugation is preferably 700-900 rpm, such as 800 rpm; the centrifugation time is preferably 1-3 min, such as 2 min; Wherein, the second washing method is preferably water washing and / or alcohol washing; the alcohol in the alcohol washing is preferably ethanol; the second washing is preferably first washed with water for 3 times, and then washed with sewage ethanol for 1 time; The drying operation is preferably vacuum drying; the drying temperature is preferably 50-70° C., such as 60° C.; and the drying time is preferably 9-11 h, such as 10 h.

6. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 5.

7. The silicon-carbon composite material according to claim 6, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1) to (7): (1) The silicon-carbon composite material comprises porous silicon and a carbon layer coated on the surface of the porous silicon; Wherein, the thickness of the carbon layer is preferably 5-15 nm, more preferably 8-12 nm, for example 11 nm; (2) The average pore size of the silicon-carbon composite material is 20-40 nm, preferably 20-35 nm, such as 20.1 or 34.7 nm; (3) The D50 of the silicon-carbon composite material is 4-6 μm, for example, 4.2, 4.6, 4.3, 5.5, 4.8 or 4.1 μm; (4) The specific surface area of ​​the silicon-carbon composite material is 60-130 m 2 / g, preferably 70-128m 2 / g, such as 73.1 or 125.4m 2 / g; (5) The mass content of carbon in the silicon-carbon composite material is 25-35%, preferably 25-30%, for example 28.77%; (6) The mass content of silicon in the silicon-carbon composite material is 60-70%, preferably 61-65%, for example 61.25%; and, (7) The mass content of oxygen in the silicon-carbon composite material is 5-12%, preferably 8-10%, for example 9.98%.

8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as claimed in claim 6 or 7.

9. Use of the electrode piece according to claim 8 in an electrochemical device.

10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 8.

Citation Information

Patent Citations

  • Silicon-containing mineral-based porous silicon-carbon composite anode material and its preparation method

    CN113871604B

  • Method for synthesizing porous silicon-carbon composite material in one step by solid phase method and application of porous silicon-carbon composite material

    CN116190656A

  • Porous silicon-carbon composite negative electrode material and preparation method and application thereof

    CN116995219A